2004
DOI: 10.1074/jbc.m405089200
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic Peptide Mimicking the Third Intracellular Loop of the V2 Vasopressin Receptor Inhibits Signaling through Its Interaction with Receptor Dimer and G Protein

Abstract: In this study, we investigated the mechanism by which a peptide mimicking the third cytoplasmic loop of the vasopressin V2 receptor inhibits signaling. This loop was synthesized as a cyclic peptide (i3 cyc) that adopted defined secondary structure in solution. We found that i3 cyc inhibited the adenylyl cyclase activity induced by vasopressin or a nonhydrolyzable analog of GTP, guanosine 5-O-(3-thio)triphosphate. This peptide also affected the specific binding of [ 3 H]AVP by converting vasopressin binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…The linear receptor analogs (MBP-I3-GGGA-Ct and MBP-I3) display higher affinity for arrestin2 (1-382) than MBP-Ct. This finding is in agreement with a report that a cyclic peptide mimicking I3 of the V2 receptor inhibits signaling (Granier et al, 2004). We also found that truncated arrestin2 demonstrates the highest affinity for V1ROSS-I3-Ct, which was designed to have I3 and Ct moieties in spatial proximity.…”
Section: Discussionsupporting
confidence: 93%
“…The linear receptor analogs (MBP-I3-GGGA-Ct and MBP-I3) display higher affinity for arrestin2 (1-382) than MBP-Ct. This finding is in agreement with a report that a cyclic peptide mimicking I3 of the V2 receptor inhibits signaling (Granier et al, 2004). We also found that truncated arrestin2 demonstrates the highest affinity for V1ROSS-I3-Ct, which was designed to have I3 and Ct moieties in spatial proximity.…”
Section: Discussionsupporting
confidence: 93%
“…Имеется много работ, авторы которых показали, что пептиды, соответствующие ЦП рецепторов, регулирующих эндокринные функции организма, активны in vitro и селективно влияют на гормональные сигнальные системы [37][38][39][40][41][42][43][44][45][46][47]. В большинстве своем они не содержат гидрофобных радикалов, и не могут быть отнесены к пепдуцинам.…”
Section: влияние на эндокринные системыunclassified
“…Considering the low amount of available structural data on entire receptors, spectroscopic studies of synthetic peptides consisting of receptor fragments provided an insightful method for the identification of the structural and functional features of the intracellular loops of GPCRs, and this method has been widely used. [18][19][20][21][22][23][24][25][26][27][28] The V2 vasopressin receptor belongs to the class A of GPCRs. It activates the GαS protein via its third intracellular loop i3 29,30 and part of its proximal Cterminal region 31 to produce its renal antidiuretic effect.…”
mentioning
confidence: 99%
“…The synthetic peptide inhibits GTP binding by the GαS protein. 20 Using a cyclized form, named thereafter i3_cyc, as a bait in a proteomic approach led to the identification of the receptor of the C1q complement (gC1qR) as an interacting protein. 32,33 gC1qR is a multifunctional and multicompartmental cellular protein.…”
mentioning
confidence: 99%